First performance test of a 25 T cryogen-free superconducting magnet. (3rd May 2017) - Awaji, Satoshi; Watanabe, Kazuo; Oguro, Hidetoshi; Miyazaki, Hiroshi; Hanai, Satoshi; Tosaka, Taizo; Ioka, Shigeru
Abstract: A 25 T cryogen-free superconducting magnet (25T-CSM) was developed and installed at the High Field Laboratory for Superconducting Materials (HFLSM), IMR, Tohoku University. The 25T-CSM consists of a high-temperature superconducting (HTS) coil and a low-temperature superconducting (LTS) coil. A high-strength CuNb/Nb3 Sn Rutherford cable with a reinforcing stabilizer CuNb composite is adopted for the middle LTS section coil. All the coils were impregnated using an epoxy resin for conduction cooling. Initially, a GdBa2 Cu3 O y (Gd123) coil was designed as the HTS insert coil, and then a Bi2 Sr2 Ca2 Cu3 O y (Bi2223) coil was also developed. The HTS insert and the LTS (CuNb/Nb3 Sn and NbTi) outsert coils are cooled by two 4K GM and two GM/JT cryocoolers, respectively. The LTS coils successfully generated a central magnetic field of 14 T at an operating current of 854 A without any training quench. The Gd123 coil generated 10.15 T at an operating current of 132.6 A in the absence of a background field. Subsequently, the operating current of the Gd123 insert was increased in a step-by-step manner under a background field of 14 T. The Gd123 coil could be operated up to 124.0 A stably, which corresponds to 23.55 T, but quenched at around 124.6 A (23.61 T). The Bi2223 insert coil using a Ni-alloy reinforced Bi2223 tape successfully generated 11.48 T at an operation current of 204.7A in a stand-alone test and 24.57 T in a background field of 14 T. The differences between the calculated and the measured values of the central magnetic fields are about 0.4 T for the Gd123 insert and 0.1 T for the Bi2223 insert around 24 T.